Simultaneous Determination of D-amino Acids in Rat Urine by Highperformance Liquid Chromatography-tandem Mass Spectrometry Method: Application to Investigate the Clinical Value of D-amino Acids in the Early Diagnosis of Alzheimer’s Disease - Zhang, Min; Zhang, Shuting; Yu, Weichao; Li, Xiaoyan; Ma, Ning; Cui, Yan (Current Pharmaceutical Analysis, 2021)
Background: D-amino acids are closely related to the development and progression of Alzheimer's disease (AD) and are expected as the novel biomarkers for AD diagnosis. Objective: The aim was to investigate the potential clinical value of D-amino acids for Alzheimer's disease. Methods: A simple and sensitive HPLC/MS-MS method was developed for the simultaneous determination of D-alanine, D-glutamine, D-proline and D-serine in rat urine. The samples were firstly pretreated by methanol, then derivatized by 7-chloro-4-nitrobenzoxadiazole with Fudosteine as internal standard, enantioseparated on Sumichiral OA-2500S column, using a mobile phase composed of acetonitrile- methanol (50:50, v/v) containing 0.5% formic acid, and detected with 4000 Qtrap MS/MS in electrospray-ionization source by negative ion mode. Results: The established method was successfully applied to determine the D-amino acid levels in rat urine from 20 Alzheimer's disease rats and 20 age-matched normal controls. The mean levels of Damino acids in the urine of Alzheimer's disease rats were all significantly lower than those in normal controls. Based on the contents of D-amino acids, the distinction model between Alzheimer's disease rats and normal controls was established by the Bayesian discriminant analysis. Conclusion: The relationship between Alzheimer's disease and D-amino acids revealed that D-amino acids would be potential biomarkers for Alzheimer’s disease.
Keywords: enantioseparation